Transparency and Confidence-Building Measures in Outer Space Activities - United Nations (United Nations, 2014)
This new Study Series (No. 34) focuses on the 2013 report of the Group of Governmental Experts on Transparency and Confidence-Building Measures in Outer Space Activities that contains the Group's conclusions and recommendations. Part 2 includes the final report of the Secretary-General containing concrete proposals from Member States on international outer space transparency and confidence-building measures, and background papers submitted by experts from Australia, Brazil, Italy, Japan, Kazakhstan and Nigeria.